2008
DOI: 10.1007/s11292-008-9058-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulated experiments and their potential role in criminology and criminal justice

Abstract: The use of computational simulations in the field of criminology and criminal justice is growing rapidly (Gunderson and Brown 2000;Liu et al. 2005;Wang 2005; Eck and Liu 2008). Some criminologists emphasize the importance of simulation methods for strengthening and elaborating theory Eck 2005;Groff 2007b), others focus on the use of simulation as a policy evaluation tool (Perez and Dray 2005). Groff (2007a), for example, created a society and then systematically varied specific conditions under which that soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Though not concerned explicitly with network structure, two previous studies of road closure, carried out by Matthews (1993Matthews ( , 1997) using a quasi-experimental design, are particularly notable for having brought about an apparent reduction in burglary, despite being focussed primarily on prostitution. A further, and complementary, possibility, would be to explore these issues further via agent-based modelling (see Groff and Mazerolle 2008). This represents a means by which the consequences of potential changes to network structure could be explored quantitatively, at low marginal cost, prior to their deployment in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Though not concerned explicitly with network structure, two previous studies of road closure, carried out by Matthews (1993Matthews ( , 1997) using a quasi-experimental design, are particularly notable for having brought about an apparent reduction in burglary, despite being focussed primarily on prostitution. A further, and complementary, possibility, would be to explore these issues further via agent-based modelling (see Groff and Mazerolle 2008). This represents a means by which the consequences of potential changes to network structure could be explored quantitatively, at low marginal cost, prior to their deployment in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Considering such complexity and the outcomes that it generates is a main strength of computational models (Epstein 1999). The application of computer simulation and agent-based models may be particularly useful in illuminating the potential outcome of the process of scaling up (Groff and Mazerolle 2008).…”
Section: Conclusion and Directions For Researchmentioning
confidence: 99%
“…As outlined by Groff and Mazerolle (2008), recent research activity within criminology and criminal justice has indicated growing support for the utility of computer-based simulations (as emphasized by the 2008 special issue of the Journal of Experimental Criminology that focused explicitly on these techniques). To date, simulation has examined a broad range of techniques and a wide spectrum of criminological issues.…”
Section: Introductionmentioning
confidence: 99%